Breast cancer incidence and mortality trends in an affluent population: Marin County, California, USA, 1990–1999 - Clarke, Christina A (BioMed Central, 2002)
BACKGROUND: Elevated rates of breast cancer in affluent Marin County, California, were first reported in the early 1990s. These rates have since been related to higher regional prevalence of known breast cancer risk factors, including low parity, education, and income. Close surveillance of Marin County breast cancer trends has nevertheless continued, in part because distinctive breast cancer patterns in well-defined populations may inform understanding of breast cancer etiology. METHODS: Using the most recent incidence and mortality data available from the California Cancer Registry, we examined rates and trends for 1990–1999 for invasive breast cancer among non-Hispanic, white women in Marin County, in other San Francisco Bay Area counties, and in other urban California counties. Rates were age adjusted to the 2000 US standard, and temporal changes were evaluated with weighted linear regression. RESULTS: Marin County breast cancer incidence rates between 1990 and 1999 increased 3.6% per year (95% confidence interval, 1.8–5.5), six times more rapidly than in comparison areas. The increase was limited to women aged 45–64 years, in whom rates increased at 6.7% per year (95% confidence interval, 3.8–9.6). Mortality rates did not change significantly in Marin County despite 3–5% yearly declines elsewhere. CONCLUSION: Patterns of breast cancer incidence and mortality in Marin County are unlike those in other California counties, and they are probably explained by Marin County's unique sociodemographic characteristics. Similar trends may have occurred in other affluent populations for which available data do not permit annual monitoring of cancer occurrence.